Use of Intensive Care Unit Diary as an Integrated Tool in an Italian General Intensive Care Unit: A Mixed-Methods Pilot Study. Issue 4 (July 2021) - Iannuzzi, Luigi; Villa, Silvia; Vimercati, Simona; Villa, Marta; Pisetti, Carmen Francesca; Viganò, Giulia; Fumagalli, Roberto; Rona, Roberto; Lucchini, Alberto
Abstract : Purpose: The aim of this study was to investigate the implementation of an intensive care unit (ICU) diary in an Italian general ICU. Methods: A mixed-methods pilot study was performed, enrolling all patients who received an ICU diary in an Italian ICU during the study period. Results: Study results are presented in 2 sections: (1) diary evaluation and content themes and (2) follow-up program results. Sixty-six patients were assessed for eligibility. Diary administration was possible in 31 patients (47%). The overall diary entries, in 31 analyzed diaries, were 1331, with a median of 25 entries (interquartile range, 16–57 entries) for each diary. Participants' relatives and friends wrote a median of 1.2 (0.3–1.6), and nurses wrote 1.1 (0.8–1.2). Other ICU staff wrote a total of 24 entries (2%). Follow-up results revealed low incidence of delirium detected in only 1 patient at the 7-day visit (3%). The median value of PTSS-10 (Post Traumatic Stress Symptoms) score was 12 (3.5–12) at the 7-day visit, 6 (1.5–12) at 3 months' telephone interview, and 12 (1.5–17) at 6 months' visit. Conclusions: To our knowledge, this is the first Italian report about the introduction of an ICU diary. The diaries were easily implemented in our clinical practice as a "low-cost" initiative. In our study, nurses and participants' relatives and friends wrote a similar number of entries in each analyzed diary. This project could be effective in reducing survivors' delirium and post-traumatic stress disorder and in implementing mutual understanding between clinical staff and relatives during ICU stay.